Political Process and Insecurity Among Youths in Oshodi-Isolo Local Government Area, Lagos - Folorunsho Muyideen Ogunmefun; Oyeyemi Tolulope Evelyn (RIRAI Publisher, 2021)
Political insecurity is an inevitable endemic menace negating human development across most of the developing nations. However, various reviewed publications posits that youths in most of all developing nations are categorized as crime prone segment of the country used by the state political actors for obstructing political process based on their perceived political vested interest. Youths in all human society are known as the catalyst for accelerating and achieving progressive socio-economic and political development if properly managed otherwise apolitical involvement of the youths in political processes will degenerate to social milieu such as civil unrest, traumatization, retrogressive economic development, death, bad national and international image among the league of nations, Anomie and structural functionalist theories were adopted Qualitative method was adopted for data collection from 40 respondents through the use of In-depth interview and purposive sampling techniques while content method of data analysis was adopted for the transcription of the data collected from the interviewees at Oshodi-Isolo, Lagos. Large numbers of the interviewees concluded that Nigeria political processes, elections, electioneering process is faulty therefore there is a needs for proper reorientation, full sensitization and socialization of Nigerian on the types of political culture and community controlling policing measure needed to foster the growth and development of political process in Nigeria More so, Nigeria youths should purged themselves out of preconceived notion that labeled them (youths) as agent of political violence or insecurity in the country so as to enjoy progressive democratic ethos